Posthumanism in Indonesian Short Stories and their Relevance to the Development of Critical Literacy - Nugraha, Dipa (SCAD Independent, 2024)
Posthumanism discusses the uncertainty of humankind’s future and the changing perspectives on humanity and life. In the Indonesian context, the issues of posthumans have not been discussed, while the usage of robot and artificial intelligence technologies has been proliferating in the related industry for several years. This article discusses two Indonesian short stories, Andina Dwifatma’s “Linus Damono” (2018) and Erwin Setia’s “Cerita Dua Robot dan Pemuda Penyendiri” (2019). Close reading is used in the data collection and analysis of the two short stories. It reveals that the short stories display non-human subjects' narratives. The two short stories also show non-human subjects that are/ are not humanistic and humans’ (total?) control over non-human subjects. Hence, the two short stories present two contradictory concerns on the projection of the human future: utopia and dystopia. The issues revealed from the short stories are essential to create awareness of the potential benefits and threats of using robotic and artificial intelligence technologies. Furthermore, this article also shows that the two short stories can be used as reading materials to develop critical literacy on posthuman issues.